Penerapan Metode Muhadatsah untuk Meningkatkan Maharah Kalam Siswa di Lembaga Kursus Bahasa Arab (LKBA) “OCEAN” Pare Kediri - Ike Nur Isnaini, Ayu; Niswah MZ. , Isniyatun (Menara Tebuireng, 2024)
Abstract— This study aims to find out how the application of the Muhadatsah method in improving students' Maharah Kalam. This research is a descriptive research that uses a qualitative approach with research subjects students at the OCEAN Pare Kediri Arabic Language Course Institute. Data collection was carried out by observation, interviews and documentation. The research results show 1). The application of the Muhadatsah Method at the OCEAN Pare Arabic Course Institute starts with the selection of teachers. Teachers must take a minimum of a 1 month course at LKBA OCEAN so they can apply muhadatsah teaching techniques starting from delivering mufrodats, talking to students using the mufrodats that are delivered, providing evaluation materials ranging from rote memorization to oral exams to students. The book used is a self-written book made by the institution namely Ustadz Thoyyib and Ustadz Wahid. As for the process of implementing learning, the teacher must have a learning plan that includes material. The muhadatsah method used by teachers at OCEAN Arabic language course institutions includes giving mufradat, memorizing, practicing Arabic, ta'aruf, presentations, debates, singing, and asking questions. 2). The first application of the muhadtasah method for students at the OCEAN Arabic Course institution is to develop the mufrodats that have been given. Second, processing words with the rules of nahwu and shorof which suit the dlomir and the other person. Third, communicate in Arabic in accordance with Arabic language courses spontaneously. And the fourth, actively speaking both inside and outside the bi'ah lughowiyah area. 3). Supporting factors in learning Arabic for students at the OCEAN Arabic Language Institute are the active Arabic language environment that is applied starting from the leaders, teachers, institutional staff and students. Adequate facilities both from buildings and learning equipment. Students have a high learning enthusiasm. The inhibiting factors were the different language backgrounds before entering LKBA OCEAN, some were already proficient and some were not proficient, and some students' memorization was weak. Keyword: Application, Muhadatsah, Maharah Kalam